A THEORETICAL DISCUSSION OF ZAKAT FOR INCOME GENERATION AND ITS FIQH ISSUES - Sarif, Suhaili; Kamri, Nor 'Azzah (Jurnal Syariah, 2009)
The use of zakat for income generation is a mechanism where zakat wealth is distributed in a way that helps eligible recipients to generate their income, so that they could be permanently independent after a specific period of time. The idea of such a mechanism, although considerably discussed by many contemporary scholars, is not totally new as it has also been briefly mentioned by some classical jurists. This article thus discusses the concept and proposed mechanism of income generation through zakat underlined by a number of modern scholars together with its related issues of fiqh. This is due to the fact that the zakat as a religious obligation must accordingly adhere to the principles underlined by Shari`ah beside any other economic objective which it strives to achieve.